2014
DOI: 10.1039/c4cc04024d
|View full text |Cite
|
Sign up to set email alerts
|

Selective photocatalytic oxidation of benzene for the synthesis of phenol using engineered Au–Pd alloy nanoparticles supported on titanium dioxide

Abstract: The selectivity of photocatalytic phenol production from the direct oxidation of benzene can be enhanced by fine adjustment of the morphology and composition of Au-Pd metal nanoparticles supported on titanium dioxide thereby suppressing the decomposition of benzene and evolution of phenolic compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 13 publications
2
26
0
Order By: Relevance
“…Hence, the adsorption of CHHP over an active site comprising neighbouring Au and Pd atoms will more favourably lead to the cleavage of the O-O bond in CHHP due to the difference in induced charge between the two metal components, which exist as a Au --Pd + couple (Scheme 1) and this we consider gives an electronic basis for the origin of the synergistic effect that is clearly observed when Pd is added to Au (and vice versa) for this, and possibly other, redox reactions. This enhancement can be observed for a broad range of Au:Pd compositions, rather than a narrow composition where synergy has been observed in previous studies for other redox reactions [15][16][17]; but clearly requires a minimum level of either metal since compositions with either low amounts of Au or Pd are ineffective in the bimetallic catalysts. Scheme 1: Specific surface substrate adsorption of CHHP in the case of a bimetallic Au-Pd catalyst (left) and non-specific surface substrate adsorption of CHHP in case of a monometallic catalyst (right).…”
Section: Mechanistic Studies Using Eprmentioning
confidence: 71%
See 1 more Smart Citation
“…Hence, the adsorption of CHHP over an active site comprising neighbouring Au and Pd atoms will more favourably lead to the cleavage of the O-O bond in CHHP due to the difference in induced charge between the two metal components, which exist as a Au --Pd + couple (Scheme 1) and this we consider gives an electronic basis for the origin of the synergistic effect that is clearly observed when Pd is added to Au (and vice versa) for this, and possibly other, redox reactions. This enhancement can be observed for a broad range of Au:Pd compositions, rather than a narrow composition where synergy has been observed in previous studies for other redox reactions [15][16][17]; but clearly requires a minimum level of either metal since compositions with either low amounts of Au or Pd are ineffective in the bimetallic catalysts. Scheme 1: Specific surface substrate adsorption of CHHP in the case of a bimetallic Au-Pd catalyst (left) and non-specific surface substrate adsorption of CHHP in case of a monometallic catalyst (right).…”
Section: Mechanistic Studies Using Eprmentioning
confidence: 71%
“…Previous studies have shown that the promising properties of Au can be manipulated by the addition of Pd to form Au-Pd bimetallic alloys as green catalysts [13][14][15][16][17]. Herein we report that Au-Pd nanoparticles supported on MgO can improve both conversion and product selectivity in the cyclohexane oxidation reaction as compared to the commercial cobalt naphthenate promoter.…”
Section: Introductionmentioning
confidence: 80%
“…The enhanced photocatalytic performance caused by the interaction between AuPd alloy and TiO 2 was also reported by Mizukoshi et al 23 Moreover, recent research on photocatalytic benzene oxidation further suggested that the interplay of AuPd alloy and TiO 2 led to a significantly improvement of selective conversion of phenol. 24 These investigations also indicate the thickness and composition of the shell layer may influence the electronic properties of the promoters. Chemical vapour impregnation (CVI) approach have been also reported as a promising technique for the decoration of semiconductor photocatalyst with surface clean metal promoter NPs.…”
Section: Introductionmentioning
confidence: 91%
“…A comparison of catalytic performance of mesoporous Au/CTAB/SiNPs catalyst with the already reported catalysts to the best of our knowledge for the benzene oxidation is given in Table 2 [9,11,14,24,29]. From the benzene conversion and phenol selectivity values, we saw that activity of mesoporous Au/CTAB/SiNPs catalyst is higher than other reported catalysts.…”
Section: Stability Of the Au/ctab/sinps Catalystmentioning
confidence: 80%
“…The hydroxylation of benzene over different catalysts is mostly taking place either peroxy hydroxyl radical (OOH Á ) formation or hydroxyl free radical (OH Á ) formation [24][25][26]. Here, in our case the initial possibility of electrostatic interaction of H 2 O 2 with the active sites of porous gold monoliths followed by the self-decomposition of H 2 O 2 via homolytic cleavage of the HO-OH bond results in the OH Á free radical species [27].…”
Section: Possible Mechanismmentioning
confidence: 97%